Analysis of the health status and its influencing factors of the low-income populations in Wuxi, China - Shiming Li; Ying Jiang; Yue Wu; Yingying Ji; Lin Tian; Queping Yang; Haohao Zhu (Frontiers Media S.A., 2024)
ObjectiveTo understand the physical health condition and its influencing factors among the low-income population.MethodLow-income residents who visited or consulted at our Hospital during 2022 were selected for this study. Through telephone or face-to-face interviews, a self-made basic information questionnaire was used for data collection. The physical health level of the low-income population was analyzed, and a logistic regression model was applied to study its influencing factors.ResultsA total of 2,307 people were included in this study, of which 2,069 had various types of diseases, indicating a disease rate of 89.68%. Multivariate logistic regression analysis showed that age ≥ 60 years old (OR = 1.567, 95%CI: 1.122-2.188), poor mental health status (OR = 2.450, 95%CI: 1.203-3.678), smoking (OR = 1.752, 95%CI: 1.269-2.206), pulse pressure difference ≥ 60 (OR = 1.485, 95%CI: 1.164-1.787), and poor hearing (OR = 1.268, 95%CI: 1.026-1.324) were risk factors for disease, whereas being female (OR = 0.729, 95%CI: 0.540-0.984) was a protective factor for physical health.ConclusionAs a developing country with a large population, we should particularly focus on the physical health issues of the low-income population, take targeted measures for disease situations, and improve the quality of life of the low-income population.